Anti-inflammatory compound curcumin and mesenchymal stem cells in the treatment of spinal cord injury in rats - Ruzicka, Jiri; Urdzikova, Lucia Machova; Kloudova, Anna; Amin, Anubhav G; Vallova, Jana; Kubinova, Sarka; Schmidt, Meic H; Jhanwar-Uniyal, Meena; Jendelova, Pavla (Acta neurobiologiae experimentalis, 2018)
Spinal cord injury leads to a robust inflammatory response that is an unfavorable environment for stem cell implantation. In this study, we evaluated the effect of combined therapy of curcumin and mesenchymal stem cells (MSC) on behavioral recovery and tissue sparing, glial scar formation, axonal sprouting and inflammatory responses in a rat experimental model of spinal cord injury (SCI). Balloon-induced compression lesion was performed at thoracic (Th8-9) spinal level. Out of the four groups studied, two groups received curcumin on the surface of the spinal cord immediately after SCI and then once a week for 3 weeks together with an intraperitoneal daily curcumin injection for 28 days. The other two groups received saline. Seven days after SCI, human MSC were intrathecally implanted in one curcumin and one saline group. Both curcumin and curcumin combined with MSC treatment improved locomotor ability in comparison to the saline treated animals. The combined treatment group showed additional improvement in advanced locomotor performance. The combined therapy facilitated axonal sprouting, and modulated expression of pro-regenerative factors and inflammatory responses, when compared to saline and single treatments. These results demonstrate that preconditioning with curcumin, prior to the MSC implantation could have a synergic effect in the treatment of experimental SCI.
Keywords: Mesenchymal Stem Cells; Curcumin; regenerace nervu; Nerve Regeneration; transplantace mezenchymálních kmenových buněk; antiflogistika; obnova funkce; modely nemocí na zvířatech; Anti-Inflammatory Agents; poranění míchy; Mesenchymal Stem Cell Transplantation; potkani Wistar; Animals; Spinal Cord Injuries; zvířata; Rats, Wistar; Recovery of Function; mezenchymální kmenové buňky; Disease Models, Animal; kurkumin